Webinar Insights: Challenges and opportunities of digital technologies for coffee value chains in Central America - Nguyen, Vi (International Food Policy Research Institute, 2023)
Digital technologies are transforming the agricultural sector and the global food system in innovative ways. From farm machinery automation to digital traceability tools to remote satellite data, the range of digital solutions available for different parts of the agri-food value chain is diverse.